Transparency through financial claims with fingerprints: A free market mechanism for preventing mortgage securitization induced financial crises - Helmut Gründl; Thomas Post (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
Lack of transparency in securitization transactions significantly contributed to the severe financial crisis of 20072009. To increase transparency we propose a new mechanism: financial claims with fingerprints. They would allow market participants at each stage of the securitization process to obtain easily full information about the underlying original risks and the superior claims that need to be satisfied before receiving their own payoffs. The fingerprint mechanism would considerably enhance transparency in securitization transactions at the expense of some transaction costs, while reducing the need for government involvement in securitization markets.
Keywords: D53; E44; G14; G18; G21; G24; G28; F34; 330; Financial crisis; securitization; mortgage-backed securities; transparency; opaqueness; Asset-backed security; Wertpapierhandel; Information; Datensicherheit; Finanzmarktkrise; Welt